Effect of an educational program on the knowledge, attitudes, and practices of hospital nurses regarding evidence-based practice: A quasi-experimental study - Omed Hamarasheed Mehammed-Ameen; Salih Ahmed Abdulla (PLoS ONE, 2026)
Background Preparing nurses for evidence-based practice (EBP) requires developing their knowledge, skills, attitudes, and ability to apply evidence-based practice in clinical settings. This study assessed the effects of an educational program on hospital nurses’ knowledge, attitudes, and practices regarding evidence-based practice. Methods A quasi-experimental study with a control group and pre–post intervention assessments. The study was conducted among 116 hospital nurses in Kirkuk City, Iraq, selected using convenience sampling (58 in the intervention group and 58 in the control group). Nurses in the intervention group participated in an educational program on evidence-based practice. Data were collected at baseline and three months post-intervention using a structured self-administered questionnaire assessing knowledge, attitudes, and self-reported practice. Results Nurses in the intervention group demonstrated statistically significant improvements in evidence-based practice knowledge, attitudes, and practices compared with baseline, while no significant changes were observed in the control group (p < 0.05). Repeated-measures ANOVA revealed a significant group × time interaction, with large effects on knowledge (η² = 0.85) and practice (η² = 0.69), and a moderate effect on attitudes toward evidence-based practice (η² = 0.13). Conclusion The educational program was associated with significant improvements in nurses’ EBP knowledge, attitudes, and self-reported practices. These findings suggest that structured EBP education can enhance nursing competencies and support the integration of evidence-based care into clinical practice.